The Commitment of Secondary School Principals in Hodeidah City to Professional Ethics from the Viewpoint of Teachers - Ahmed, Sadiq Abbas Saeed; Ameen, AbdulJabbar AlTayeb (Journal of Educational and Psychological Sciences, 2024)
The study aims to identify the commitment of secondary school principals in Hodeidah City to professional ethics from the viewpoint of teachers. To achieve the objectives of the research, the researcher used the descriptive analytical approach, and a questionnaire was made containing (30) items distributed over three axes: professional ethics towards (teachers – students – local community institutions), and the research sample amounted to (58) male and female teachers. The results of the study revealed: that the reality of the commitment of secondary school principals in Hodeidah City to professional ethics from the point of view of teachers was high for all axes with an arithmetic average of (3.99). In addition, there were no statistically significant differences between teachers’ estimates of the degree of commitment of secondary school principals in Hodeidah City to the ethics of school administration, due to the academic qualification variable in all axes, as well as to the gender variable for all axes. On the other hand, there are statistically significant differences in the axis of local community institutions in the gender variable in favor of males.
Keywords: ethics of secondary school principals; secondary school principals